2019
DOI: 10.1016/j.ijengsci.2019.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Anti-plane surface waves in media with surface structure: Discrete vs. continuum model

Abstract: We present a comparison of the dispersion relations derived for anti-plane surface waves using the two distinct approaches of the surface elasticity vis-a-vis the lattice dynamics. We consider an elastic half-space with surface stresses described within the Gurtin-Murdoch model, and present a formulation of its discrete counterpart that is a square lattice half-plane with surface row of particles having mass and elastic bonds different from the ones in the bulk. As both models possess anti-plane surface waves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…Mishuris et al (2007Mishuris et al ( , 2009 ;Slepyan (2002); Sharma (2015aSharma ( , 2017c; Porubov and Andrianov (2013); Porubov et al (2018); Gorbushin et al (2018), where the efficiency of discrete lattice models is demonstrated. As an example, we recently provided the comparison of the surface wave propagation within the Gurtin-Murdoch model and the lattice dynamics which shows similarities in dispersion relations for both models after some re-scaling, see Eremeyev and Sharma (2019). Thus, the lattice dynamics can serve as a counterpart of continuum surface elasticity models.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mishuris et al (2007Mishuris et al ( , 2009 ;Slepyan (2002); Sharma (2015aSharma ( , 2017c; Porubov and Andrianov (2013); Porubov et al (2018); Gorbushin et al (2018), where the efficiency of discrete lattice models is demonstrated. As an example, we recently provided the comparison of the surface wave propagation within the Gurtin-Murdoch model and the lattice dynamics which shows similarities in dispersion relations for both models after some re-scaling, see Eremeyev and Sharma (2019). Thus, the lattice dynamics can serve as a counterpart of continuum surface elasticity models.…”
Section: Introductionmentioning
confidence: 99%
“…Following Eremeyev and Sharma (2019) here we discuss the anti-plane surface waves propagation in an elastic half-space with a piece-wise inhomogeneity in surface properties. We consider a square lattice which consists of material particles of mass M and stiffness of bonds K, where the surface consists of material particles of two kind which both are different from the ones in the bulk.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within this context of surface induced phenomena, the present paper extends the applications of recent framework developed for discrete scattering problems [33,34,43]. In contrast to the recent investigation of the wave transmission of surface localized anti-plane shear wave [42] in lattice structures, motivated by certain discrete counterpart [8] of Gurtin-Murdoch model [11,12,45,46], the present paper applies similar methodology to reveal the transmission characteristic associated with a close-up of discrete form of surface roughness.…”
Section: Introductionmentioning
confidence: 96%